Epigenetic Alterations in Podocytes in Diabetic Nephropathy - Erina Sugita; Kaori Hayashi; Akihito Hishikawa; Hiroshi Itoh (Frontiers Media S.A., 2021)
Recently, epigenetic alterations have been shown to be involved in the pathogenesis of diabetes and its complications. Kidney podocytes, which are glomerular epithelial cells, are important cells that form a slit membrane-a barrier for proteinuria. Podocytes are terminally differentiated cells without cell division or replenishment abilities. Therefore, podocyte damage is suggested to be one of the key factors determining renal prognosis. Recent studies, including ours, suggest that epigenetic changes in podocytes are associated with chronic kidney disease, including diabetic nephropathy. Furthermore, the association between DNA damage repair and epigenetic changes in diabetic podocytes has been demonstrated. Detection of podocyte DNA damage and epigenetic changes using human samples, such as kidney biopsy and urine-derived cells, may be a promising strategy for estimating kidney damage and renal prognoses in patients with diabetes. Targeting epigenetic podocyte changes and associated DNA damage may become a novel therapeutic strategy for preventing progression to end-stage renal disease (ESRD) and provide a possible prognostic marker in diabetic nephropathy. This review summarizes recent advances regarding epigenetic changes, especially DNA methylation, in podocytes in diabetic nephropathy and addresses detection of these alterations in human samples. Additionally, we focused on DNA damage, which is increased under high-glucose conditions and associated with the generation of epigenetic changes in podocytes. Furthermore, epigenetic memory in diabetes is discussed. Understanding the role of epigenetic changes in podocytes in diabetic nephropathy may be of great importance considering the increasing diabetic nephropathy patient population in an aging society.